Penguatan Integritas Pelajar SMAN 34 Jakarta Melalui Sosialisasi Hukum dan Antikorupsi untuk Indonesia Emas 2045 - Alicia Christine Laubura; Zahwa Cantika Putri Rafian; Naqiyyah Azzahra; Rashif Aliftiar Rizqullah; Subakdi, Subakdi; Mulyadi, Mulyadi; Hasan Basri; Ronald Manalu (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Corruption has been a well-known problem in Indonesia for a long time. News of corruption cases often becomes a hot topic, especially in this digital age where information spreads rapidly. Unfortunately, statistics show that public reaction to corruption cases in 2024 was more permissive than in the previous year. This is undoubtedly a hindrance in realizing the vision of Indonesia Gold 2045. Therefore, as one of the efforts, a socialization on law enforcement and anti-corruption was conducted at SMA Negeri 34 Jakarta on October 15, 2024, aiming to create a young generation that is law-abiding and anti-corruption. In this activity, students were invited to understand corruption in depth, including the legal basis, the impact of corruption, and how to prevent the seeds of corruption from an early age. Using an interactive and engaging approach, as well as examples of familiar corruption cases, students not only learned about the law, but also developed an awareness of the importance of maintaining integrity in their daily lives.